Pull-up 운동 시 그립 두께에 따른 근활성도의 변화 - 서상원; 고성식; 안근옥 (Exercise science (Seoul, Korea), 2021)
PURPOSE:There are various variables such as exercise posture, exercise intensity, number of repetitions, and rest time of training for muscle strength development, and these variables are intended to stimulate muscle activity. The purpose of this study was to examine the effects of muscle activation according to grip thickness in pull-up exercise. METHODS: Eleven healthy men were randomly crossover design assigned to pull-up exercise (concentric: 1-s, eccentric: 1-s, 2-s/repetition) to failure. Surface electromyography (EMG) was recorded from the forearm flexors/extensors, biceps brachii, trapezius middle/ lower and latissimus dorsi for muscle activation. Using the resulting EMG data, which were filtered of electromyogram artifacts, we calculated the root mean squares (RMS). RESULTS: Dependent-sample t-test produced a result, muscle activity in forearm flexors (p<.01), biceps brachii (p<.01), trapezius middle (p<.01), trapezius lower (p<.01) and latissimus dorsi (p<.05) were significantly increased at thick grip compared to normal grip in pull-up exercise. CONCLUSIONS:This study suggested that the thicker the grip, the higher the muscle activation. Using a grip thickness as one of the variables for training programs is considered as a method to stimulate muscle activity. KCI Citation Count: 0